Logan Medallist 2. Geophysics and Geology: An Essential Combination Illustrated by LITHOPROBE Interpretations–Part 1, Lithospheric Examples - Clowes, Ron (Geoscience Canada, 2015)
Lithoprobe (1984–2005), Canada’s national, collaborative, multidisciplinary, Earth science research project, investigated the structure and evolution of the Canadian landmass and its margins. It was a highly successful project that redefined the nature of Earth science research in Canada. One of many contributions deriving from the project was the demonstration by example that Earth scientists from geophysics and geology, including all applicable subdisciplines within these general study areas, must work together to achieve thorough and comprehensive interpretations of all available data sets. In this article, I exemplify such contributions by summarizing interpretations of lithospheric structure and development from Lithoprobe journal publications relating to eleven specific regions in Canada. Four of the examples derive from studies in the Mesozoic–Cenozoic Canadian Cordillera: the original Lithoprobe program on Vancouver Island, the region of the Monashee Mountains in the southeastern Cordillera, allochthonous and autochthonous terranes in the northwestern Cordillera, and the craton- Cordillera transition in northeastern British Columbia. Two examples represent the Paleozoic Appalachians in Newfoundland. One of these shows crustal structure across the southwestern part of the island; the other shows a more detailed study on the southwestern coast. The Mesoproterozoic Grenville Province is the focus of two examples. One shows crustal structure from the Archean Pontiac metasedimentary sub-province across the Grenville Front and the exposed southeastern part of the province; the other illustrates two- and three-dimensional interpretation in the central Grenville Province. Lithoprobe supported research in the development of geodynamical modelling techniques and the application of these to tectonic processes inferred within transect study areas. Such work is exemplified through a comparison of a numerical model developed for the southwestern Grenville orogen and comparison of model results with those from geophysical and geological studies. Lithoprobe carried out extensive research in the Paleoproterozoic Trans-Hudson Orogen in Saskatchewan and Manitoba. Some early results from the interpreted seismic results completely revised previous results based on geology only and fostered additional geological studies. This is illustrated by studies over an Archean window in the middle of the orogen. The final example derives from studies in the westernmost part of the Archean Superior Province in western Ontario. It focuses on the derivation of near-surface velocity information from the seismic reflection data and the relationship of this information to the known geology.